Comparative Evaluation of Socioscientific Issues in Secondary Physics Curriculum and Textbooks - Sevim Bezen (e-Kafkas Eğitim Araştırmaları Dergisi)
Socioscientific issues (SSI) provide an essential framework for understanding and managing the effects of scientific research and technological developments in physics on society. In this study, it was aimed to comparatively evaluate the secondary physics curriculum (9th, 10th, 11th and 12th grades) published in 2018 in Turkey and the 9th, 10th, 11th and 12th-grade physics textbooks approved by the Ministry of National Education within the framework of this curriculum in terms of SSI. A qualitative research method was utilised in the study. The study's data source comprised a secondary physics curriculum and textbooks. The research data were analysed using document analysis. As a result of the study, it was determined that only 14 out of 213 objectives in the secondary physics curriculum contained SSI content. It was determined that the grade level with the most socioscientific content was nine and then 12. In the study, as a result of the comparative analysis of the secondary physics curriculum and physics textbooks, it was determined that there was no equivalent for an outcome in the 9th-grade physics textbook that included SSI content in the curriculum. In this context, this study determined that the current education reform is incompletely reflected in the textbooks. Based on this, it can be suggested that the secondary physics course curriculum updated in 2024 is aimed to present a curriculum that includes objectives that will support students to understand the social, environmental and ethical dimensions of scientific knowledge, to increase the SSI content in the curriculum and to enrich physics textbooks with examples and activities with SSI content in line with the curriculum.